COMPARATIVE STUDY ON THE LITERATURE AND LANGUAGES OF EUROPE, AMERICA AND AUSTRALIA - Xoldorova Shahlo Shuhratjon qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This study provides a comparative analysis of the literature and languages of Europe, America, and Australia. It investigates how historical developments, colonization, migration, and globalization have shaped the linguistic and literary landscapes of these regions. The paper highlights the coexistence of dominant and minority languages, the role of indigenous literatures, and the evolving identity of national literary traditions. Through qualitative analysis of literary trends, language use, and sociolinguistic factors, the study reveals both convergent and divergent patterns of literary and linguistic development across the three regions.